Clinical use of mean platelet volume and neutrophil-to-lymphocyte ratio to predict prognosis in heart failure with preserved ejection fraction patients. (3rd October 2022) - Menghoum, N; Beauloye, C; Lejeune, S; Gruson, D; Pasquet, A; Vancraeynest, D; Gerber, B; Bertrand, L; Horman, S; Pouleur, A C
Abstract: Background: Over the last decade, a new paradigm for heart failure with preserved ejection (HFpEF) development has been proposed. High burden of comorbidities would lead to a systemic inflammatory state and enhanced platelet activation. High platelet reactivity could be associated with higher mean platelet volume (MPV) due increased circulating immature platelets. Moreover, neutrophil-to-lymphocyte (NLR) reflects systemic inflammation. Both parameters have been associated with morbidity and mortality in heart failure (HF). However, data in HFpEF are limited. Purpose: We aim to investigate the use of MPV and NLR to predict clinical outcome in HFpEF patients. Methods: We prospectively enrolled 228 patients with HFpEF (79±9 years, 66% female patients) and 38 controls of similar age and gender (78±5, 63% female patients). All subjects underwent a complete two-dimensional echocardiography. Mean platelet volume and NLR were measured at baseline. Patients were followed over time for a primary end point of all-cause mortality or first HF hospitalization. The prognosis impact of MPV and NLR were determined with Cox proportional hazard models. Results: Mean MPV and median NLR were significantly higher in HFpEF patients compared to controls (MPV: 11.7±1.1 fL vs 10.0±1.1 fL, p=0.005; NLR: 3.3 [2.2; 5.0] vs 2.2 [1.9; 2.9], p<0.001). HFpEF patients with MPV >75th percentile (n=56) had more frequently a history of ischemic cardiomyopathy (46%, p=0.04). HFpEF patients with NLR >75th percentile (n=57) were more frequently in New York Heart Association functional (NYHA) III or IV class (58%, p=0.02) and had higher levels of NT-proBNP (2152 [1336; 6397] pg/mL vs 1690 [705; 3304] pg/mL, p=0.02). Over a median follow-up of 26 months [11.5–56.7 months], 136 HFpEF patients (60%) reached the composite end point (87 deaths and 107 hospitalizations for HF). In univariate Cox regression analysis for the primary end point, MPV >75th percentile (HR: 1.45 [0.99; 2.13], p=0.05) and NLR >75th percentile (HR: 1.59 [1.11; 2.28], p=0.01) were predictors of the primary composite endpoint. In multivariate Cox regression analysis, mean platelet volume >75th percentile (χ 2 =8.11, P=0.004), continuous MPV (χ 2 =4.64, P=0.03) provided significant additional prognostic value over a baseline model created using independent predictors of the primary composite end point: body mass index (BMI), NYHA class III or IV, chronic obstructive pulmonary disease (COPD), loop diuretics, estimated glomerular filtration rate (eGFR) and NT-proBNP. By contrast, NLR did not provide any additional information (Figure 1 and 2). Conclusion: MPV level and NLR were significantly higher in HFpEF patients compared with controls of similar age and gender. Elevated MPV offers an additional prognostic indication for clinicians and more interestingly it supports the hypothesis that of platelet activation could be involved in disease pathophysiology in HFpEF. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Fondation Saint-Luc